1, 3-Bis(4′-carboxylatophenoxy)benzene and 3, 5-bis(1-imidazoly)pyridine derived Zn(ii)/Cd(ii) coordination polymers: synthesis, structure and photocatalytic properties. Issue 22 (25th May 2021) - Gong, Qin; Wang, Jun; Shi, Chuncheng; Liu, Qiang-Qiang; Lu, Lu; Singh, Amita; Kumar, Abhinav
Abstract : Zn(ii ) and Cd(ii )-based CPs derived from a 1, 3-bis(4′-carboxylatophenoxy)benzene and 3, 5-bis(1-imidazoly)pyridine synthesized and their photocatalytic properties for decomposition of methylene blue investigated. Abstract : Coordination polymers (CPs) have emerged as a peculiar category of multidimensional materials used as photocatalysts for assorted classes of lethal aromatic dyes. Herein, two new d 10 -configuration based coordination polymers with formula [Zn(L)(bip)·H2 O] (1 ) and [Cd3 (L)3 (bip)2 (H2 O)2 ] (2 ) (H2 L = 1, 3-bis(4′-carboxylatophenoxy)benzene and bip = 3, 5-bis(1-imidazoly)pyridine) have been reported and characterized using microanalyses, FTIR and single crystal X-ray diffraction. The X-ray analysis reveals that the Zn(ii ) based CP 1 has a 2D supramolecular framework built by hydrogen bonds as well as packing interactions between adjacent chains having a 3-nodal topology with a Schläfli notation of (4·8 4 ·12)(4)(8). Meanwhile, the Cd(ii ) based CP 2 exhibits a three-dimensional (3D) 2-fold interpenetrating network, having a 4, 6-c net topology with a Schläfli notation of (4 4 ·6 10 ·8)(4 4 ·6 2 ). Both the materials have been used as photocatalysts for UV light assisted photodegradation of aromatic dye methylene blue (MB). The photocatalysis experiments indicate that the percentage degradation of MB is 35.92% and 72.02% in the presence of CPs 1 and 2, respectively, for a time period of 100 min, while in the absence of these CPs the percentage degradation is merely 11.49%. A mechanistic study towards understanding of the photocatalytic degradation of MB was carried out using LC–MS studies and computationally using band gap calculations; a probable mechanistic pathway has also been proposed which was further complimented with Hirshfeld surface analysis.